Climate Services for Resilient Development (CSRD) Technical Exchange in Eastern Africa Workshop Report - Owusu, Aisha; Tesfamariam Tekeste, Yohana; Ambani, Maurine; Zebiak, Stephen E.; Thomson, Madeleine C. (2017)
In 2005, the International Research Institute for Climate and Society published its assessment of key gaps in the use of climate information for health, agriculture, water and other sectors in countries across Africa. The results from the report were less than stellar. After an extensive review of use of climate information in the development sectors of Africa, the authors concluded that the continent suffered from “market atrophy” – the reinforcing effect of zero effective supply of climate information and zero effective demand. Twelve years later, organizations such as the IRI, CSRD, CCAFS, ICPAC, and UKMO have made enormous strides at increasing both climate information supply and demand through the implementation of climate data platforms and the organizing of capacity-building seminars. In order to capitalize on the presence of the many climate and sector experts from across the IGAD region, the organizations above held a joint event, the Climate Services for Resilient Development (CSRD) Technical Exchange workshop, in Zanzibar on August 23-25, 2017, immediately after the 47th Greater Horn of Africa Climate Outlook Forum (GHACOF47). The workshop was designed to offer potential and existing users a platform to voice their needs for the development and better use of historical, monitored and forecast information for the management of drought across climate-sensitive sectors.